2014
DOI: 10.1136/bcr-2014-205529
|View full text |Cite
|
Sign up to set email alerts
|

Hantavirus: an infectious cause of acute kidney injury in the UK

Abstract: We present a case of an undifferentiated febrile illness in a 59-year-old man from East Yorkshire. He was initially treated for leptospirosis due to the fact that he had farm exposure and the findings of acute kidney injury (AKI), thrombocytopenia and a raised alanine transferase (ALT) on his initial blood results. Serology tests later proved him to have had another rodent-borne illness: hantavirus. An investigation by Public Health England (formerly known as Health Protection Agency) (PHE) went on to prove th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…On the other hand, CKDu in Sri Lanka is known to develop from tubular damage [34,35]. Several Old World hantaviruses have been reported to cause AKI but not HFRS [36]. Furthermore, it has been reported that chronic proteinuria continues even several years after recovery from hantavirus infection [32,37].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, CKDu in Sri Lanka is known to develop from tubular damage [34,35]. Several Old World hantaviruses have been reported to cause AKI but not HFRS [36]. Furthermore, it has been reported that chronic proteinuria continues even several years after recovery from hantavirus infection [32,37].…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, a Yorkshire famer was later proven by IFA and SIA to have contracted SEOV-HFRS. Like his Northern Irish colleagues 20 years earlier, leptospirosis was originally suspected, but not confirmed [108]. However, a brown rat on his farm yielded in RT-PCR an amplicon having 97% nucleotide sequence similarity with the British laboratory rat SEOV strain IR461, and resulted in a second British SEOV isolation, called Humber virus.…”
Section: Overview Of Chronological Seov Findings By Continentmentioning
confidence: 99%
“…12 In 2011, a 59-year-old man who worked on a rat-infested pig farm in Yorkshire, GB, was diagnosed with SEOV-HFRS, and SEOV was detected in wild rats from the same pig farm. 16 However, very little is known about SEOV in British wild rats in terms of distribution or prevalence and therefore the public health risk is unclear. In this report, we describe a study of hantavirus surveillance in wild brown rats in Northern England and Wales in order to begin to better understand the epidemiology of this infection, and therefore its public health risk.…”
Section: Introductionmentioning
confidence: 99%